Cross-Sector Collaboration and Socio-Economic Growth: The Practices of Entrepreneurial Universities - Khie, Sak; Lindawati, Lindawati; Listiorini, Dewi (Indonesian Association for Public Administration (IAPA), 2024)
The higher education role is evolving from focusing on teaching, research, and innovation to becoming a key player in shaping and influencing the entrepreneurial ecosystem. This article used the systematic literature review (SLR) method to investigate how entrepreneurial universities can encourage collaboration across sectors to drive socio-economic growth. Based on the results of identification, screening and eligibility checking of 1375 documents, 30 articles discussing entrepreneurial universities and collaboration were examined. The collaborations are driven by addressing societal issues, fostering innovation, developing commercial potential, and gaining access to funding or subsidy programs, with the role of universities strengthened by regulations on ownership of intellectual property and distribution of royalties to inventors. Collaboration is also related to the university's ability to encourage innovation and connect it with the market and the institutional framework. In addition, entrepreneurship training, apart from being closely linked to applied research, encourages academics to turn their business plans into start-up ventures. In this context, government institutions have a passive role in collaboration. Thus, to enhance a sustainable and impactful entrepreneurial ecosystem, policymakers are urged to foster an entrepreneurial and innovative culture, create conducive environments for start-up and MSME growth, and encourage active collaboration and contributions from all stakeholders.